GPS: A Randomized Controlled Trial of Sexual Health Counseling for Gay and Bisexual Men Living With HIV. Issue 1 (January 2021) - Hart, Trevor A.; Noor, Syed W.; Skakoon-Sparling, Shayna; Lazkani, Samer N.; Gardner, Sandra; Leahy, Bob; Maxwell, John; Julien, Rick; Simpson, Scott; Steinberg, Malcolm; Adam, Barry D.
Abstract: Gay, bisexual, and other men who have sex with men (GBM) continue to have high rates of HIV and sexually transmitted infections, including syphilis. GBM have therefore been identified by public health agencies as a high-priority population to reach with prevention initiatives. Despite the importance of mental health in preventing HIV and related infections, there is a shortage of credentialed mental health professionals to deliver behavioral Counseling interventions. The current study evaluated the efficacy of GPS, a community-based and peer-delivered sexual health promotion motivational interviewing–based intervention for HIV-positive GBM who engaged in condomless anal sex (CAS) in the past 2 months. GPS prevention counseling demonstrated a 43% relative reduction at 3-month follow-up in CAS with serodiscordant partners and significant reductions in sexual compulsivity. The study demonstrated that community-based counselors can administer an efficacious motivational interviewing program, and suggests a continued benefit of counseling methods to promote the sexual health of higher risk populations. Highlights: Community-based counselors administered this motivational interviewing program. The program, called GPS, was efficacious in reducing sexual compulsivity. The GPS program was also efficacious for reducing sexual risk behavior. Behavioral counseling can promote the sexual health of at-risk populations.